Working women, caring men, and the family bank: Ideal gender relations after the Washington Consensus dans Developing partnerships: gender, sexuality, and the reformed World Bank - Bedford, Kate (Developing partnerships: gender, sexuality, and the reformed World Bank, 2009)
A critique of how the World Bank encourages gender norms, Developing Partnerships argues that financial institutions are key players in the global enforcement of gender and family expectations. By combining analysis of documents produced and sponsored by the World Bank with interviews of World Bank staffers and case studies, Kate Bedford presents a detailed examination of gender and sexuality in the policies of the world’s most influential development institution.
Section: xxxiv, 292 pages : illustrations
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; féminisme décolonial; histoire et politique; inégalités; pol4022; premier cycle; périodes historiques; racisme; régions géographiques; science politique; science politique et droit; sciences de la gestion; sud global; systèmes d'oppressions; thématiques; économie

<< Empowerment >>: genealogie d'un concept cle du discours contemporain sur le developpement - Calves, A.-E. (REVUE TIERS MONDE, 2009)
La notion d’ « empowerment » occupe aujourd’hui une place de choix dans le discours en vogue des institutions internationales sur la « participation des pauvres » au développement. L’article retrace l’histoire du mot dans le champ du développement international : ses origines et ses sources d’influence, son émergence dans les théories des féministes du Sud et des activistes radicaux dans les années 1980, puis son institutionnalisation progressive dans le vocable politique des organismes internationaux de développement. L’article montre comment avec sa cooptation, l’empowerment passe d’un processus de conscientisation et de mobilisation politique venant de la base et visant la transformation radicale des structures de pouvoir inégalitaires, à un concept vague et faussement consensuel, qui assimile le pouvoir aux choix individuels et économiques, dépolitise le pouvoir collectif, et est instrumentalisé pour légitimer les politiques et les programmes de développement top-down existants.
Disponible en ligne à https://shs-cairn-info.proxy.bibliotheques.uqam.ca/revue-tiers-monde-2009-4-page-735?lang=fr&tab=texte-integral
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; féminisme décolonial; histoire et politique; justice sociale; militance; néolibéralisme; pol4022; premier cycle; périodes historiques; relations internationales; ressource en ligne; science politique; science politique et droit; sciences humaines; sociologie; systèmes d'oppressions; thématiques

« EMPOWERMENT »: GÉNÉALOGIE D'UN CONCEPT CLÉ DU DISCOURS CONTEMPORAIN SUR LE DÉVELOPPEMENT - Calvès, Anne-Emmanuèle (Revue Tiers Monde, 2009)
La notion d'« empowerment » occupe aujourd'hui une place de choix dans le discours en vogue des institutions internationales sur la « participation des pauvres » au développement. L'article retrace l'histoire du mot dans le champ du développement international : ses origines et ses sources d'influence, son émergence dans les théories des féministes du Sud et des activistes radicaux dans les années 1980, puis son institutionnalisation progressive dans le vocable politique des organismes internationaux de développement. L'article montre comment avec sa cooptation, l'empowerment passe d'un processus de conscientisation et de mobilisation politique venant de la base et visant la transformation radicale des structures de pouvoir inégalitaires, à un concept vague et faussement consensuel, qui assimile le pouvoir aux choix individuels et économiques, dépolitise le pouvoir collectif, et est instrumentalisé pour légitimer les politiques et les programmes de développement top-down existants.
Keywords: 1900-1999; 1980-1989; 1990-1999; approches et analyses; cours; discipline; développement; empowerment; féminisme décolonial; histoire et politique; pol4022; premier cycle; périodes historiques; régions géographiques; science politique; sud global; système colonial; systèmes d'oppressions; thématiques

Sous le regard de l'Occident : recherche féministe et discours colonial - Mohanty, Chandra Talpade (Sexe, race, classe pour une épistémologue de la domination, 2009)
L’analyse de la construction intellectuelle et politique des « féminismes du tiers-monde » implique nécessairement deux mouvements simultanés : d’une part, une critique interne des féminismes « occidentaux » hégémoniques et, d’autre part, la formulation de problématiques et de stratégies féministes autonomes et ancrées géographiquement, historiquement, culturellement. Le premier mouvement consiste à déconstruire et décomposer ; le second, à concevoir et construire.
Première publication: 1984
Keywords: approches et analyses; cours; discours dominant; droits des femmes*; fem1000; féminisme décolonial; féminisme postcolonial; histoire et politique; incontournable; premier cycle; privilèges; systèmes d'oppressions; thématiques

Les subalternes peuvent-elles parler? - Spivak, Gayatri Chakravorty..; Vidal, Jérôme.. (Éd. Amsterdam, 2009)
Dans le cadre d'un dialogue critique avec Michel Foucault, Gilles Deleuze et la tradition marxiste, G.C. Spivak articule le concept de subalterne (à ne pas confondre avec les notions de minoritaire ou d'opprimé) et s'interroge sur les femmes subalternes du tiers-monde, l'unification des subalternes au sein d'une communauté.
Keywords: approches et analyses; arts; care; com5170; corps; cours; discipline; féminisme décolonial; har4600; histoire et politique; incontournable; oui; premier cycle; thématiques; études littéraires; études postcoloniales

Genre et développement : Enjeux et luttes des femmes du Tiers-monde dans Introduction au développement international: approches, acteurs et enjeux - Martinez, A.; Beaudet, Pierre; Haslam, Paul Alexander; Schafer, Jessica (Introduction au développement international: approches, acteurs et enjeux, 2008)
Section: x, 507 pages : illustrations, cartes ; 24 cm
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; développement; féminisme décolonial; histoire et politique; pol4022; premier cycle; privilèges; périodes historiques; régions géographiques; science politique; sud global; systèmes d'oppressions; thématiques

Firekeepers of the twenty-first century: First Nations women chiefs - Voyageur, Cora Jane (McGill-Queen's University Press, 2008)
A quiet revolution is occurring in Canada's First Nations communities, with changes taking place on social, political, and economic fronts and a significant redistribution of power. Changes to the Indian Act in 1951 paved the way for women to become officially involved in reserve politics, and with governments responding to the demand of First Nations for self-government, positions once held exclusively by men are now being filled by women. Beginning with Elsie Knott, the first female chief in Canada, Cora Voyageur presents the lives of sixty-four of the ninety women chiefs who have assumed the traditionally male role of elected First Nations leadership. Using a range of qualitative research strategies, surveys, participant observation, interviews, and discussions with focus groups, Voyageur presents the colonial histories behind the issues that contemporary Aboriginal communities struggle with and delineates the resulting leadership dilemmas for chiefs, while also articulating a story that is unique to First Nations women. Voyageur asks women chiefs about what inspired them to become leaders, how they've maintained their priorities, and the personal and professional costs and rewards involved in their positions. Firekeepers of the Twenty-First Century is a groundbreaking work that examines the experiences of women as they negotiate multiple roles and navigate the worlds of gender, race, and reserve politics.
Section: xxi, 157 pages
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; entretien; femmes* au pouvoir; femmes* autochtones; féminisme autochtone; féminisme décolonial; gouvernance; histoire et politique; militance; pol4105; pouvoir; premier cycle; premières nations; périodes historiques; régions géographiques; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques

Genre, mouvements populaires urbains et environnement - Verschuur, Christine (Graduate Institute Publications, 2007)
Le désordre urbain et les défis environnementaux que nous connaissons ne sont pas perçus ni vécus pareillement aux Suds et aux Nords, par les femmes et les hommes, par les puissants et les exclus. Les mouvements populaires urbains et de lutte pour l'environnement participent de la réflexion sur les changements de paradigme de développement qui sont urgents et nécessaires. La perspective de genre donne des clés de lecture pour comprendre comment les asymétries féminin-masculin structurent la perception et l’organisation concrète de la vie sociale. La forte présence des femmes dans les organisations urbaines et de lutte pour l’environnement est généralement peu ou pas reconnue. Ce livre explore certains mouvements populaires urbains, qui participent au travail de prise de conscience et de revendications de droits et qui permettent ainsi d'envisager des alternatives sur des territoires de vie, sans plus attendre.
Keywords: 2000 à aujourd'hui; approches et analyses; changements climatiques; environnement; féminisme décolonial; histoire et politique; intersectionnalité; justice climatique; justice sociale; outils; ouvrages de références; projet charge mentale; périodes historiques; thématiques; écoféminisme

‘Who is the Developed Woman?’: Women as a Category of Development Discourse, Kumaon, India - Klenk, Rebecca M. (Development and Change, 2004)
This article analyses gendered discourses of development in rural North India, and addresses the usefulness of recent scholarship on development as ‘discourse’ for understanding connections between development and subjectivity. This scholarship is an excellent point of departure for exploring the contradictions inherent in the institutionalization of economic development and the global reach of its discourses, but it has focused primarily upon development as discourse at official sites of deployment, while paying less attention to how specific discourses and processes of development are appropriated by those constituted as beneficiaries of development. The under-theorization of this aspect has meant that the range of processes through which development projects may encourage new subject positions are poorly understood. By investigating what some women in rural Kumaon have made of their own development, this article contributes to emerging scholarship on development and subjectivity with an ethnographic analysis of the polysemic enthusiasm for development expressed by some of its ‘beneficiaries’.
Keywords: Kumaon; anthropologie; approches et analyses; asie; cours; discipline; développement; féminisme décolonial; histoire et politique; inde; pol4022; premier cycle; relations internationales; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; thématiques

Creating a critical faith-centered space for antiracist feminism: Reflections of a muslim scholar-activist - Zine, Jasmin (Journal of Feminist Studies in Religion, 2004)
Keywords: antiracisme; approches et analyses; cours; discipline; fem3400; féminisme décolonial; histoire et politique; premier cycle; racisme; ressource en ligne; science des religions; sciences humaines; système colonial; systèmes d'oppressions; thématiques

Feminist postcolonial theory: A reader - Lewis, Reina; Mills, Sara (Edinburgh University Press, 2003)
Les lectures ont été choisies pour examiner la nature textuelle et discursive du discours colonial et postcolonial en relation avec le genre et les effets matériels de la condition postcoloniale et des pratiques développées en relation avec celle-ci.
https://search.ebscohost.com/login.aspx?direct=true&scope=site&db=nlebk&db=nlabk&AN=2398481
Keywords: approches et analyses; cours; cycles supérieurs; fem1000; fem7000; féminisme décolonial; genre; histoire et politique; identités LGBTQIA2+; lit3220; premier cycle; ressource en ligne; thématiques

Feminism without borders decolonizing theory, practicing solidarity - Mohanty, Chandra Talpade (Duke University Press, 2003)
"Bringing together classic and new writings of the trailblazing feministtheorist Chandra Talpade Mohanty, Feminism Without Borders addresses someof the most pressing and complex issues facing contemporary feminism. Forgingvital links between daily life and collective action and between theory andpedagogy, Mohanty has been at the vanguard of Third World and internationalfeminist thought and activism for nearly two decades. This collection highlightsthe concerns running throughout her pioneering work: the politics of differenceand solidarity, decolonizing and democratizing feminist practice, the crossingof borders, and the relation of feminist knowledge and scholarship to organizingand social movements. Mohanty offers here a sustained critique of globalizationand urges a reorientation of transnational feminist practice towardsanticapitalist struggles. Her probing and provocative analyses of key conceptsin feminist though - "home", "sisterhood", "community"–Lead the way toward a feminism without borders, afeminism fully engaged with the realities of a transnational world."
Keywords: anticapitalisme; approches et analyses; cours; discours dominant; fem1000; féminisme décolonial; féminisme postcolonial; histoire et politique; premier cycle; privilèges; systèmes d'oppressions; thématiques; transnationalisme

« Sex and the City » : la prostitution à l’ère des migrations mondiales - Robinson, Lillian S. (Recherches féministes, 2002)
Comme caractéristique du développement capitaliste, la migration économique a toujours entraîné le travail sexuel. À l’heure de la mondialisation, cela signifie pour beaucoup de femmes, qui émigrent du village à la grande ville dans leur propre pays ou du pays natal à l’étranger, un choix imposé par les circonstances. Cet article examine surtout la décision d’émigrer, les moyens empruntés et la situation à l’étranger de celles - la grande majorité, d’ailleurs – qui n’ont pas été victimes d’un trafic, mais qui ont exercé ce choix imposé. Le rôle dans l’émigration des travailleuses sexuelles et des clients « émigrés » en tant que touristes sexuels fait partie de la discussion, ainsi que d’autres caractéristiques économiques et culturelles.Summary As a feature of capitalist development, economic migration has historically entailed sex work as one of its components. In the age of globalization, this means a forced choice for many women, as they move from the village to the city in their own countries and across international borders. The present article focuses on the decision making process, the means of migration, and the experience in the urban site, national or international, of those – the vast majority – who have not been "trafficked", but have made this forced choice their life strategy. The impact on sex worker migration of customer "migration" in the form of sex tourism is discussed, along with the other economic and cultural factors.
Keywords: 1900-1999; afrique; amériques; approches et analyses; asie; capitalisme; cours; discipline; droits des femmes*; europe; féminisme du sud; féminisme décolonial; globalisation; his4860; histoire et politique; immigrantes clandestines; immigration; inde; industrie du sexe; inégalités; migration; pauvreté; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sexisme; sociologie; système colonial; systèmes d'oppressions; thématiques; tourisme sexuel; travail; travail des femmes*; travail du sexe

Identités et altérités : formes et discours - Institut de recherches et d'études féministes (FéminÉtudes, 2001)
Cette publication analyse les formes et discours des identités et altérités de genres. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Disponible en libre accès : https://iref.uqam.ca/feminetudes/vol-6-no-1-2001-identites-et-alterites-formes-et-discours/
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; discours; décolonialisme; féminisme décolonial; féminétudes; genre; histoire et politique; identités LGBTQIA2+; militance; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques

Strange encounters: embodied others in post-coloniality - Ahmed, Sara (Routledge, 2000)
"Examining the relationship between strangers, embodiment and community, Strange Encounters challenges the assumptions that the stranger is simply anybody we do not recognize and instead proposes that he or she is socially constructed as somebody we already know. Using feminist and postcolonial theory this book examines the impact of multiculturalism and globalization on embodiment and community whilst considering the ethical and political implication of its critique for post-colonial feminism. A diverse range of texts are analyzed which produce the figure of 'the stranger', showing that it has alternatively been expelled as the origin of danger - such as in neighbourhood watch, or celebrated as the origin of difference - as in multiculturalism. The author argues that both of these standpoints are problematic as they involve 'stranger fetishism'; they assume that the stranger 'has a life of its own'". – Site de l'éditeur.
Keywords: approches et analyses; corps; cours; discipline; féminisme décolonial; histoire et politique; lit4700; philosophie; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; études culturelles

Post-colonial studies: The key concepts - Ashcroft, Bill; Griffiths, Gareth; Tiffin, Helen (Routledge, 2000)
This volume provides an essential key to understanding the issues which characterise post-colonialism, explaining what it is, where it is encountered and why it is crucial in forging new cultural identities. As a subject, post-colonial studies stands at the intersection of debates about race, colonialism, gender, politics and language. In the language of post-colonial studies, some words are new, others are familiar words charged with new significance.
https://doi-org.proxy.bibliotheques.uqam.ca/10.4324/9780203449974
Keywords: approches et analyses; cours; discipline; fem1000; féminisme décolonial; histoire et politique; intersectionnalité; littérature; premier cycle; ressource en ligne; thématiques; études culturelles; études littéraires

« Propositions, stratégies et méthodes alternatives » dans Le genre un outil nécessaire: introduction à une problématique - Dawn; Association femmes et développement; Espace femmes international (Association) (Le genre un outil nécessaire: introduction à une problématique, 2000)
Les Cahiers Genre et Développement sont un recueil de documents de référence sur la notion de genre et l'analyse des problèmes de développement qu'elle permet. Différents thèmes sont abordés dans ce numéro : Genre et développement : une histoire déjà longue ; Le genre : une notion complexe et évolutive ; Relations de genre, relations de pouvoir ...
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; discipline; développement; féminisme décolonial; histoire et politique; pol4022; premier cycle; périodes historiques; racisme; régions géographiques; science politique; sud global; système colonial; systèmes d'oppressions; thématiques

Feminism and the body - Schiebinger, Londa (Oxford University Press, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Section: IX, 500 pages : illustrations ; 22 cm
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme